A LINGUISTIC–SEMANTIC ANALYSIS OF THE PHRASE LAA ILAHA ILLALLAH IN KITAB AT-TAWHID AND ITS IMPLICATIONS FOR ARABIC LANGUAGE EDUCATION - Muhammad Nafis; Muhammad Azriel Dzikra Mirzady; Agung Pranoto Kadiatmaja (Universitas Islam Negeri Palopo, 2025)
This study examines the linguistic and semantic structure of the phrase Laa Ilaha Illallah as presented in Kitab at-Tawhid by Muhammad bin Abdul Wahhab and explores its implications for Arabic language education. Employing a qualitative linguistic research design with a descriptive–analytical approach, the study analyzes how grammatical structure contributes to meaning construction in classical Arabic texts. The primary data consist of the phrase Laa Ilaha Illallah and its explanations in Kitab at-Tawhid, which is treated as a source of authentic classical Arabic language data rather than as a purely theological work. The findings show that the phrase is built upon a distinctive grammatical structure combining total negation through lā an-nāfiyah lil-jins and exclusive affirmation through exception (istithnā’). This structure produces semantic restriction (ḥaṣr) that is encoded directly in the syntactic configuration, demonstrating how meaning in Arabic is often conveyed through grammatical mechanisms rather than lexical elaboration. The analysis of Kitab at-Tawhid further reveals consistent patterns of linguistic explanation, including structural emphasis and repetition, which function to stabilize semantic interpretation in classical Arabic discourse. From an educational perspective, the study highlights the pedagogical potential of using linguistically rich classical expressions as instructional resources in Arabic language education. The phrase Laa Ilaha Illallah provides an effective example for teaching Arabic grammar, semantics, and reading comprehension in an integrated and contextualized manner. By emphasizing the relationship between grammatical form and meaning through authentic texts, this study contributes to the development of more analytical, meaningful, and text-based approaches to Arabic language teaching.